Articulating a life worth living: the affective morality of married women’s suicide tales in Delhi-NCR - Krishan, A (2022)
Indian women's suicide s account for over a third of female suicides globally, yet this phenomenon is mostly unknown and has yet to enter mainstream discourses within the country (India State Level Disease Burden Initiative Suicide Collaborators 2018; Mayer 2016a). Through an ethnographic study set in the country’s National Capital Region (NCR), this thesis analyses urban women’s narratives about observed or known instances of suicide. Such suicide narratives act as a space for women to reflect on the worth wholeness of gendered lives.